2014
DOI: 10.1186/1476-4598-13-129
|View full text |Cite
|
Sign up to set email alerts
|

MUC16 (CA125): tumor biomarker to cancer therapy, a work in progress

Abstract: Over three decades have passed since the first report on the expression of CA125 by ovarian tumors. Since that time our understanding of ovarian cancer biology has changed significantly to the point that these tumors are now classified based on molecular phenotype and not purely on histological attributes. However, CA125 continues to be, with the recent exception of HE4, the only clinically reliable diagnostic marker for ovarian cancer. Many large-scale clinical trials have been conducted or are underway to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
360
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(364 citation statements)
references
References 166 publications
(179 reference statements)
2
360
1
1
Order By: Relevance
“…CA125 was firstly detected in ovarian cancer and had been reported to be positive in 80% of ovarian epithelial tumor patients (10). In addition, the positive observation of CA125 is also seen in breast cancer, pancreatic cancer, gastric cancer, and some other tumors (11). Carcinoembryonic antigen (CEA) is a nonspecific tumor marker and is commonly used for detection of colorectal cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…CA125 was firstly detected in ovarian cancer and had been reported to be positive in 80% of ovarian epithelial tumor patients (10). In addition, the positive observation of CA125 is also seen in breast cancer, pancreatic cancer, gastric cancer, and some other tumors (11). Carcinoembryonic antigen (CEA) is a nonspecific tumor marker and is commonly used for detection of colorectal cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified TTN somatic mutations in multiple cancer types including melanoma, glioblastoma and pancreatic carcinoma, suggesting that the cellular functions of these molecules could possibly be related to a common tumor progression mechanism (Balakrishnan et al, 2007). MUC16 performs a number of important biological roles in cancer cell signaling, metastasis, regulation of immune responses and in anti-cancer therapeutic strategies (Felder et al, 2014). Also of note, we observed that CSMD3 harbored more mutations in Luad than in other types of cancer; in fact, 44% of Luad patients were found to have mutations in the CSMD3 region.…”
Section: Identification Of the Genes-in-common Harboring The Most Mutmentioning
confidence: 99%
“…It is a well-established biomarker used to monitor the progression and recurrence of ovarian cancer. Furthermore, it is overexpressed in a range of human malignancies including ovarian, pancreatic, breast, cholangiocarcinoma, cervical, gastric and non-small cell lung cancer [1][2][3][4][5][6]. Mucins are a family of high molecular weight glycoproteins composed of oligosaccharides attached to a peptide core [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several hundred oligosaccharides are attached to the N-terminal domain through O-linked glycosylation and N-linked glycosylation whilst the tandem repeat region (TRR) has approximately 60 repeats of a 156 amino acid sequence, with disulphide bonds that confers structural stability. Attached to the TRR is a smaller C-terminal domain that also contains a cytoplasmic tail involved in intracellular cell events ( Figure 1) [1,3,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation